Colombia Public Finance Review - World Bank (Washington, DC, 2022)
Over the past twenty years, fiscal policy has become one of the three pillars of macroeconomic stability for Colombia, the other two being the flexible exchange rate and inflation targeting. The credibility and sustainability of fiscal policy is the result of strong institutions (in particular, the fiscal rule and the medium-term fiscal and expenditure framework) and a prudent management of public finances. After the 1999 crisis, Colombia managed to reduce the general government deficit and built buffers, which allowed it to respond to the 2008 Global Financial Crisis. Colombia successfully withdrew the 2008–09 deficit expansion and ran one of the highest fiscal balances in Latin America, until the COVID-19 crisis hit. The COVID-19 crisis has created a large shock to the economy and to public finances .Growth contracted to a minimum not seen in over 35 years. The economic contraction and the response needed to address the health emergency and to sustain activity pushed the central government’s deficit and the debt to their highest levels in decade, 7.8 and 64 percent of GDP respectively. Gains in poverty reduction reached over the past 10 years were wiped off.